METAPHOR ANALYSIS OF TEACHERS’ ROLES IN THE LESS COMMONLY TAUGHT EUROPEAN LANGUAGES PROGRAMS IN CHINA - Lu, Yan; Kangro, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Teachers’ individual understanding of the roles in their own profession influences the construction of teacher-student and other work relationships. It is also an important indicator for language program managers to perceive the teaching and learning process. Metaphor analysis is an effective method to raise awareness and reflection of professional roles among teachers. This study employs the open-ended questionnaire to investigate the professional roles of the teachers in the Less Commonly Taught European Languages (LCTELs) programs in China. The framework provided by De Guerrero and Villamil’s research is adapted to design and conduct the questionnaire. The elicited metaphors are collected, categorized and analysed, to answer the research questions: (1) How do the participants metaphorically conceptualize themselves as a LCTELs teacher? (2) Is their perception of roles consistent with the results generated in the previous researches about EFL/ESL practice? (3) Are teachers’ actual and expected professional roles identical? The final 38 collected metaphors were classified into 9 categories. The results either proved the metaphors of some traditional teaching roles in the previous researches, or presented the new ones which rooted in the unique practice of the LCTELs programs.